Characteristics and Postharvest Technology of Fresh-Cut Fruits and Vegetables - nFN Qanytah; Ridwan Rachmat; Irpan Badrul Jamal (Buletin Teknologi Pasca Panen, 2013)
The increasing demand for ready to eat fresh fruits and vegetables, has increased demand for fresh cut fruits and vegetables. Supply for fresh cut fruits and vegetables is still facing many problems due to their short shelf life and changes in nutritional composition and taste. This is because plant tissue is a living tissue that can isolate many reactions and substrates. Plant tissues of fresh cut products may be wounded plant tissue during grading, sorting, washing, trimming, slicing, packaging, transporting, and loading processes. Physical, physiological, and chemical processes may occur as a result of tissue wounding. Understandiing of these characteristics would help select appropriate technologies to maintain the product quality and to prolong their shelf life. The effects of physiological, chemical, and microbiological processes on fresh cut product could be minimized by treatment such as acidification, edible coating, natural antimicrobial, firming agents, modified atmosphere packaging, low temprature, and heat treatments. Abstrak Versi IndonesiaKarakteristik Dan Teknologi Penanganan Produk Buah Dan Sayuran Terolah Minimal (Fresh Cut)Meningkatnya permintaan buah dan sayuran segar yang dapat dikonsumsi secara langsung berdampak pada peningkatan permintaan terhadap produk buah dan sayuran terolah minimal (fresh cut). Penyediaan produk buah dan sayuran terolah minimal masih banyak menghadapi kendala terkait umur simpannya yang pendek dan mudah mengalami perubahan komposisi kandungan gizi dan rasa. Hal ini terjadi karena jaringan tumbuhan merupakan jaringan hidup yang dapat mengisolasi berbagai reaksi dan substrat. Dalam proses penanganan produk terolah minimal terjadi luka pada jaringan tanaman, baik yang disengaja maupun yang tidak disengaja. Luka dapat terjadi dalam proses grading, sortasi, pencucian, pengupasan, pemotongan, pengemasan, transportasi, dan proses bongkar muat. Pada jaringan tanaman yang mengalami luka tersebut, Pengetahuan tentang perubahan karakteristik tersebut diperlukan sebagai dasar pemilihan teknologi yang tepat untuk mempertahankan mutu dan penggunaan edible coating, anti mikroba alami Firming Agent, Modified Atmosphere Packaging. perlakuan dingin, dan perlakuan panas.